ASSOCIATION OF PLASMA LEPTIN AND OMENTIN-1 WITH ORAL VITAMIN D INTAKE IN PATIENTS WITH CORONARY ARTERY DISEASES - Nazar, Shazia; Hina Abbas, Syeda; Sana Abbas, Syeda (Annals of Allied Health Sciences, 2024)
Objective: To evaluate the association of oral vitamin D intake on leptin & omentin-1 circulating levels in patients diagnosed with coronary artery disease. Material & Methods: The study was conducted at the Cardiology unit of Civil Hospital Karachi. A total count of 200 diagnosed patients of coronary artery disease with insufficient vitamin D and were prescribed oral vitamin D by their doctors, were selected for the study. Patients were assigned to the daily dose of 2000IU vitamin D for 8 weeks. Anthropometric measurements and circulating vitamin D, omentin-1 & leptin levels were assessed at the beginning and post-treatment. Results: A notable decrease in leptin (3776 ± 0.422 vs. 3187 ± 0.144, p<0.001), omentin-1 (245 ± 26.1 vs. 296.5 ± 28.11, p < 0.001), and high density lipoprotein levels (36.80 ± 13.46 vs. 45.2 ± 14.31, p < 0.001) were found after oral vitamin D intake. Conclusion: Vitamin D supplements over an 8-week period substantially reduced serum levels of leptin, whereas they raised omentin-1 and high density lipoprotein levels in coronary artery disease patients.